Evaluation Of Growth And Yield Performances Of Napier Grass Cultivar Pakchong-1 Under Different Spacial Patterns In The Kilinochchi District, Sri Lanka - Sathees, D.; Sivajanani, S. (University of Colombo Institute for Agro-Technology and Rural Sciences, 2022)
Inadequacy of quality forage production is a major limiting factor for dairy production in the Sri Lankan dry zone. Napier grass cv Pakchong-1 (Pennisetum purpureum x Pennisetum glaucum) is a tropical grass with fastgrowing and high yielding ability. The study aims to determine the growth parameters and yield performance of Pakchong-1 grass under three different spacing of 30cm x 30cm, 90cm x 90cm and 120cm x 90cm in the Kilinochchi district, dry zone of Sri Lanka, from April 2019 to March 2020. A complete randomized design with three replicates was used in this study. Growth parameters were measured bi-weekly up to the 8th week and harvested the foliage after the 8th week in 56 days intervals. Plants at 30cm x 30cm spacing have shown the highest plant height of (153.00cm), the higher number of leaves (93.67), longer leaf length (95.33cm), wider leaf width (3.82cm)and higher leaves per tiller (11.33) at 8 weeks after planting (P<0.05). While the highest (P<0.05) the number of tillers (10.00) was recorded at 120cm× 90cm spacing. Fresh matter yields were highest (P<0.05) at 30cm x 30cm spacing in all cutting frequencies. The second cutting at the 14th week has shown the highest fresh matter yield(P<0.05) in all spacing. Pakchong – 1 can be suggested for the Sri Lankan dry zone regions at 30cm x 30cm spacing to provide the highest fresh matter output and optimal growth performance.
Keywords: Dry Matter; Growth parameters; Kilinochchi district; Pakchong-1 (Pennisetum purpureum × Pennisetumglaucum